Vécu Des Enfants Soldats Pendant La Guerre: Une Analyse À Partir Des Projets De l’Organisation Non Gouvernemental Caritas Makeni En Sierra Léone - Ossi, Gnamien Yawa (European Scientific Journal, ESJ, 2017)
The phenomenon of «child soldier» has become very rampant these last years. In Africa, they are very common in the Democratic Republic of Congo (DRC), in Chad, in Uganda, in Sierra Leone, and in Côte d’Ivoire. More recently, they are in Mali and in the Central African Republic. However, armed conflicts have imposed various situations on populations. The children are the main victims. The focus of this study is on child soldiers during times of war. The main objective of this study is to analyze the ways they join the armed groups and the difficulties of their social reintegration. The objective of this study is to analyze the recruitment conditions of children and the difficulties of social reintegration. The hypothesis postulates that there is a link between the passage of the children in armed groups and their psychosocial outcome. The study took place in Sierra Leone. The quantitative and qualitative methods were used. The results of the study show that: the mode of recruitment of children has an influence on their social reintegration. Also, the violent practices in armed conflicts are obstacles to their social reintegration.